THE IMPACT OF VIRTUAL VIDEO PROJECT ON STUDENTS’ ENGLISH LEARNING ENGAGEMENT - Asfihana, Raida; Rafiqa, Rafiqa; Iskandar, Iskandar; Rahayu, Puji Sri; Fuentes, Anne Shangrila (LLT Journal: A Journal on Language and Language Teaching, 2024)
This paper examines how Project-Based Learning (PjBL) affects students' engagement in English when taught in a virtual learning environment. The case study was classroom-based and used data collected through interviews with twenty-five participants engaged in a virtual PjBL enactment. The data were analyzed using thematic analysis, while member checking was also used to ensure the data’s trustworthiness. The study found that the PjBL enactment had improved students’ learning engagement in three ways. First, the cognitive impact was seen in the participants’ experiences of a culture of self-directed learning where they were involved in the inquiry process through scaffolding activities. Second, their behavioral engagement was seen in their active involvement in project presentations and their shift in attitude towards the use of technology in virtual PjBL. Finally, their emotional engagement was reflected in the increased personal self-esteem and the change in the lecturer-student interaction. This research suggests that PjBL should be used more extensively in virtual classrooms because it positively impacts the students’ learning engagement and boosts their motivation to learn English.